2009
DOI: 10.1111/j.1364-3703.2009.00535.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative trait loci meta‐analysis of Plum pox virus resistance in apricot (Prunus armeniaca L.): new insights on the organization and the identification of genomic resistance factors

Abstract: Plum pox virus (PPV) is responsible for sharka disease, one of the most detrimental stone fruit diseases affecting Prunus trees worldwide. Only a few apricot cultivars have been described as resistant, most originating from North American breeding programmes. Several PPV resistance quantitative trait loci (QTLs) have been mapped in various progenies, consistently highlighting the contribution to the resistance of the upper part of linkage group 1 (LG1). However, to date, no consensus has been reached on the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 36 publications
(98 reference statements)
4
56
1
1
Order By: Relevance
“…Meta-QTL analysis has also been successfully conducted in several other crops like maize Truntzler et al, 2010;Hao et al, 2010;Li et al, 2011;Wang et al, 2006;Coque et al, 2008), cotton (Rong et al, 2007), rice (Ballini et al, 2008;Norton et al, 2008;Khowaja et al, 2009), rapeseed (Shi et al, 2009), potato (Danan et al, 2011), cocoa (Lanaud et al, 2009), soybean (Guo et al, 2006;Sun et al, 2012) and apricot (Marandel et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Meta-QTL analysis has also been successfully conducted in several other crops like maize Truntzler et al, 2010;Hao et al, 2010;Li et al, 2011;Wang et al, 2006;Coque et al, 2008), cotton (Rong et al, 2007), rice (Ballini et al, 2008;Norton et al, 2008;Khowaja et al, 2009), rapeseed (Shi et al, 2009), potato (Danan et al, 2011), cocoa (Lanaud et al, 2009), soybean (Guo et al, 2006;Sun et al, 2012) and apricot (Marandel et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Harlayne four distinct dominant resistance QTLs, three on linkage group 1 (LG 1) and one QTL on LG 3. Molecular studies of Marandel et al (2009) proved different PPV behaviour of cv. Harlayne from other PPV resistant apricot cultivars.…”
Section: Discussionmentioning
confidence: 96%
“…This conclusion is in agreement with the fact that Sicard et al (2008) experimented with apricot cv. Goldrich, susceptible to PPV-M. Only Marandel et al (2009) used in molecular studies of PPV resistance quantitative trait loci (QTLs) not only apricot cvs SEO and Goldrich but also cv. Harlayne.…”
Section: Discussionmentioning
confidence: 99%
“…Four quantitative trait loci (QTLs) were identified of which three mapped on linkage group 1 (LG1) which explained between 5 and 39% of the phenotypic variance. This happened when analyzing quantitative resistance of Harlayne cultivar in a large F1 population [44]. Dondini et al established that a major QTL for resistance to both PPV-M and PPV-D strains was found in the top half of "Lito"…”
Section: Kostina Et Al Compared the Inheritance Of Dormancy Length Imentioning
confidence: 99%
“…The main QTL on LG1 was upheld by Sicard et al [51] establishing new microsatellite (SSR) markers flanking the QTL and by Lalli et al [52] in a backcross population of SEO 9 Vestar and was again confirmed by Soriano et al [46] in the extended F2 Lito selfed progeny. Most of the resistance determinants shown above were characterized using the PPV-D strain as a source of inoculum and, at present, the only resistances specific to the PPV-M strain are those endorsed in the BC1 SEO xVestar [52] and in P. davidiana [44].…”
Section: Kostina Et Al Compared the Inheritance Of Dormancy Length Imentioning
confidence: 99%